Improved modelling method of Pogo analysis and simulation for liquid rockets. (February 2015) - Wang, Qingwei; Tan, Shujun; Wu, Zhigang; Yang, Yunfei; Yu, Ziwen
Abstract: An improved modelling method for Pogo analysis and simulation is presented which derives differential equations instead of the differential-algebraic equations by Rubin׳s method. Firstly the classification mechanism based on the description of independent weight-displacements is proposed and nine types of independent elements are derived by division and combination of the basic physical elements. Then the differential equations of the propulsion system are established using assembly conditions that perturbational pressures on the nodes are equal to each other. The differential equations of the Pogo analysis model are then obtained by coupling the structure vibration equations and the propulsion system equations. Since the improved Pogo analysis model does not contain algebraic equations, it can be directly used for time-domain simulation and frequency-domain analysis. Moreover, the dimensions of the improved Pogo analysis model are reduced to almost half of the ones of Rubin׳s method due to the elimination of variables of perturbational pressures, which significantly improves the numerical efficiency and stability. Finally, analysis and simulation results of a certain type of CZ rocket of China confirm the correctness and practicability of the proposed modelling method. Highlights: ● The differential equations of the Pogo analysis model are directly derived. ● The model can be used for time-domain simulation and frequency-domain analysis. ● The perturbational pressures on the nodes are eliminated in an aggregation process. ● The dimensions of the model are about one-half of the ones of Rubin׳s model.